Persistence and Mobility of Imidacloprid and Abamectin Residues in Green House Soil - Haddad, Marwan; Khalaf, Osama; Jodeh, Shehdeh (Journal of Environmental Science and Engineering Technology, 2014)
Two pesticides were selected, imidacloprid (Konfidor ®) and abamectin (Vertimec ®) which are widely used in controlling insects and pests in greenhouses in Palestine. Imidacloprid and Abamectin adsorption onto greenhouse soil surfaces was studied by batch experiments. Experiments were conducted in a set of 100 mL capped conical flasks. In each pesticide adsorption experiment, an aliquot (50 mL) of (10-50 mg/L) solutions was used. Pesticides concentration was analyzed at the end of each experiment. The results indicate that: (1) the degradation of Imidacloprid and Abamectin soils was fitted to the second-order reaction kinetics model and showed good performance for all treatments, (2) the GUS values obtained for Imidacloprid and Abamectin were ranging between 1.95 and 3.3 and 1.68 to 3.31, respectively which is rated moderate to slightly high leachable/transportable to groundwater [understanding], (3) the distribution coefficient for both tested pesticides exhibit increasing adsorption on soil surface with increasing concentration in solution, (4) the observed persistence, half-life for Imidacloprid and Abamectin was 61 and 41 days, respectively, and in good agreement with reported in literature values, (5) mobility rate constants (Kd of 2 to 11 and Koc of 142 to 817) obtained for both Imidacloprid and Abamectin were higher than those reported in literature revealing that the tested soil is higher in leaching capacity, (6) the risk of particle-bound pesticide transport through soil to groundwater was rated slightly high to high for both pesticides, and (7) mobility and persistence results of Imidacloprid and Abamectin on soil obtained in this study were highly influenced by soil composition of high silt and low organic matter content leading to lower sorption rates and higher leaching to groundwater.